Analysis and verification methods of abnormal data of coal mine safety monitoring system - XING Chengcheng (Gong-kuang zidonghua, 2017)
Three most common types of pseudo data and the causes were analyzed taking gas data as an example, and starting from demand of data analysis and pseudo data identification in upgrading program of coal mine safety monitoring system. For the pseudo data generated by sensor calibration, it is proposed to add calibration experiment specifically for identification of the pseudo data. For the pseudo data generated by electromagnetic interference, a method of simulating gas concentration value of the interference point by embedding error code in sensor program is proposed. For the pseudo data generated by transmission or equipments failure, a method of randomly manufacturing sensor or transmission line failure and observing the data processing results is proposed. The effectiveness and feasibility of the proposed methods were verified by simulation test of safety monitoring system of a certain manufacturer.